Multimodal image-guided ablation on management of renal cancer in Von-Hippel-Lindau syndrome patients from 2004 to 2021 at a specialist centre: A longitudinal observational study. Issue 3 (March 2022) - Chan, Vinson Wai-Shun; Lenton, James; Smith, Jonathan; Jagdev, Satinder; Ralph, Christy; Vasudev, Naveen; Bhattarai, Selina; Lewington, Andrew; Kimuli, Michael; Cartledge, Jon; Wah, Tze Min
Abstract: Objectives: To analyse the safety, technical feasibility, long-term renal function and oncological outcome of multimodal technologies in image-guided ablation (IGA) for renal cancer in Von-Hippel-Lindau (VHL) patients, and to evaluate factors that may influence the outcome. Methods: Retrospective analysis of a prospective database of VHL patients who underwent IGA at a specialist centre. Patient's demographics, treatment energy, peri-operative outcome and oncological outcomes were recorded. Statistical analysis was performed to determine factors associated with complication and renal function reduction. The overall, 5 and 10-year cancer specific (CS), local recurrence-free (LRF) and metastasis-free (MF) survival rates were presented with Kaplan-Meier Curves. Results: From 2004 to 2021, 17 VHL patients (age 21–68.2) with a mean (±SD) RCC size of 2.06 ± 0.92 cm received IGA. Median (IQR) RCCs per patient was 3 (2–4) over the course of follow up. Fifty-four RCCs were treated using radiofrequency ablation (n = 11), cryoablation (n = 38) and irreversible electroporation (n = 8) in 50 sessions. Primary and overall technical success rate were 94.4% (51/54) and 98% (53/54). One CD-III complication with proximal ureteric injury. Five patients in seven treatment sessions experienced a >25% reduction of eGFR immediately post-IGA. All patients have preservation of renal function at a median follow-up of 79 (51–134) months. The 5 and 10-year CS, LRF and MF survival rates are 100%, 97.8% and 100%. Whilst, the 5 and 10-year overall survival rate are100% and 90%. Conclusion: Multimodal IGA of de novo RCC for VHL patients is safe and has provided long term preservation of renal function and robust oncological durability.